Pengaruh antara Price Value dan Social Influence Terhadap Intention to Use Aplikasi Seabank - Zafirah Sabrina; Desma Noor Putri; Imelda Bella Clarisa; Mulia Warahma (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This study aims to analyze the effect of price value and social influence on intention to use on the Seabank platform. This study took a sample of respondents who were at least 17 years old and had an interest in using the Seabank application. This study obtained data through an online survey or via Google form with a target data obtained of 100 respondents, then the data was processed using SmartPLS with the SEM-PLS method. The results show that Price Value has a positive and significant influence on Behavioral Intention, Social Influence has a positive and significant influence on behavioral intention, Price Value has a positive and significant influence on Social Influence.